Połączenie klasycznego i nieklasycznego podejścia w celu wykrywania niejednorodności wariancji składników losowych modelu ekonometrycznego - Grześkowiak, Alicja (A Combination of Classical and Non-Classical Approach to Disturbance, 2008)
In this paper a concept of heteroscedasticity character determination in the linear econometric model is presented. The suggested method combines classical approach (hypothesis testing) with the maximum likelihood discriminant rule. The suggested solution is illustrated by the empirical analysis of models describing real and expected incomes of Poles.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 27, s. 19-27